Taurine supplementation can increase lipolysis and affect the contribution of energy systems during front crawl maximal effort - De Carvalho, Flávia G. [UNESP] (2018)
Taurine can affect the energy system metabolism, specifically the lipid metabolism, since an increase in lipid oxidation may promote carbohydrate savings. We hypothesized that taurine supplementation associated with high-intensity exercise could increase levels of lipolysis, benefiting swimmer performance. Nine male competitive swimmers performed two 400-m front crawl maximal efforts with a 1-week washout, and the athletes received 6 g of taurine (TAU) or placebo (PLA) supplementation 120 min before performing the effort. Oxygen consumption and the contribution of the energy systems were analyzed post effort using a Quark CPET gas analyzer. Blood samples were collected before, and 5 min post the effort for taurine and glycerol analysis. Immediately before and 3, 5, and 7 min post the effort, blood samples from the earlobe were collected to determine lactate levels. An increase of 159% was observed in taurine plasma levels 120 min post ingestion. Glycerol levels were higher in both groups post effort; however, the TAU condition promoted an 8% higher increase than the PLA. No changes were observed in swimmer performance or lactate levels; however, the percentage change in lactate levels (∆[La−]) was different (TAU: 9.36 ± 2.78 mmol L−1; PLA: 11.52 ± 2.19 mmol L−1, p = 0.04). Acute taurine supplementation 120 min before performing a maximal effort did not improve swimmer performance; however, it increased glycerol plasma levels and reduced both the ∆[La−] and lactic anaerobic system contribution.